Post a New Question

Math

posted by .

Explain how to do this with steps please.

1. Simplify cos(x-y)+cos(x+y)/cosx

I did some of these so far, don't know if it is correct.


Formula: cosxcosy= cos(x+y)+cos(x-y)/2

cos(x-y)+cos(x+y)/cosx

=cosxcosy/2cosx

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Trig

    prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
  2. Pre-Calc

    Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
  3. calc.- trig substitution

    s- integral s 1/ [ (x^4) sq.rt(x^2+9)] i know x=3tanx sq.rt(x^2+9)= 3 secx dx= 3/[cos^2(x)] so far i know: = 1/ (3tan^4(x)) 3secx cos^2(x)) dx =1/ 81 [ (sin^4 (x)/cos^4 (x)) (1/cosx) (cos^2(x))] then i'm not really sure what to do …
  4. pre-cal

    Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos 6x can be expressed as a series of terms that involve sin x or cos x only, but the end result is not a simplification. sin 2x = 2 sinx cosx cos 6x = 32 cos^6 x -48
  5. Math help again

    cos(3π/4+x) + sin (3π/4 -x) = 0 = cos(3π/4)cosx + sin(3π/4)sinx + sin(3π/4)cosx - cos(3π/4)sinx = -1/sqrt2cosx + 1/sqrt2sinx + 1/sqrt2cosx - (-1/sqrt2sinx) I canceled out -1/sqrt2cosx and 1/sqrt2cosx Now …
  6. RESPONSE to PreCalc Question

    h t t p : / / w w w . j i s k h a . c o m / d i s p l a y . c g i ?
  7. Calc.

    Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x) (dy/dx)-(dx/du)= …
  8. calculus

    Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x) (dy/dx)-(dx/du)= …
  9. Math

    Explain how to do this with steps please. 1. Simplify cos(x-y)+cos(x+y)/cosx Formula: cosxcosy= cos(x+y)+cos(x-y)/2 cos(x-y)+cos(x+y)/cosx =cosxcosy/2cosx
  10. Math, please help

    Which of the following are trigonometric identities?

More Similar Questions

Post a New Question